VARIASI TUTUR ANAK PADA MASYARAKAT BILINGUAL: STUDI KASUS ANAK USIA 8 TAHUN PADASEBUAH KELUARGA DI KOTASBMARANG - Catur Kepirianto (KAJIAN SASTRA, 2010)
Purpose of the research is to know the child language acquisition, particularly on child speech variation. Subject of the research are 8-year-old children live in an bilingual, informal Indonesian and Javanese family. Their parents are Javanese both ethnic and vernacular, otherwise they tends to speak informal Indonesian and Javanese to the subjects. The method of collecting data is simak libat cakap, participant observation and the method of analyzing data is padan pragmatik, pragmatic identity method. Result of the research is that the child speech variation is bilingual, informal Indonesian and Javanese. It likes the speech of the child invironment. Structurally, the child vocabularies and sentences are short and brief in form and it is the characteristic of the informal speech. Child speech variation is influenced by the speech variation in the child invironment. The child acquires the speech variation they listen and acquire in their speech.